Substance P induced by peripheral nerve injury in primary afferent sensory neurons and its effect on dorsal column nucleus neurons - Noguchi, K (J Neurosci, 1995)
Using in situ hybridization and the retrograde tracer, Fluorogold, we examined the expression of preprotachykinin (PPT) mRNA in the rat dorsal root ganglion neurons projecting to the gracile nucleus. Seven days after unilateral sciatic nerve transection, some medium- to large- sized neurons in the rat dorsal root ganglia projecting to the gracile nucleus express PPT mRNA, whereas very few gracile nucleus-projecting neurons on the contralateral side express PPT mRNA. Immunohistochemistry revealed an increase in substance P (SP) immunoreactivity in the gracile nucleus and large myelinated fibers in the dorsal root 2 weeks after unilateral sciatic nerve transection. The results suggest that medium to large DRG cells that project to the gracile nucleus express PPT mRNA de novo in response to peripheral nerve injury, and increased SP is transported to the gracile nucleus through large myelinated fibers. To determine whether the increased SP might affect the excitability of the gracile nucleus neurons postsynaptically, Fos expression after electrical stimulation of the injured sciatic nerve was examined. Multiple injections of the NK-1 receptor antagonist, CP-96,345, suppressed stimulus-induced Fos expression in gracile nucleus neurons including thalamic relay neurons. The inactive enantiomer, CP-96,344, had no effect on stimulus-induced Fos expression. These data indicate that the de novo synthesized SP in the lesioned primary afferent neurons may be involved in an augmentation of excitability in the dorsal column-medial lemniscus sensory pathway. This hyperexcitability may play a role in the pathogenesis of abnormal neuropathic sensations following peripheral nerve injury.